Spin squeezing as a measure of entanglement in a two-qubit system - Messikh Azeddine, Azeddine; Ficek, Zbigniew; Wahiddin, Mohamed Ridza (American Physical Society, 2003)
The relationship between entanglement and spin squeezing parameters in the two-atom Dicke system was examined. Characterizing the spin squeezing parameters by the density matrix elements, simple models of driven two-atom Dicke systems in which spin squeezing and entanglement arise dynamically were studied. It was found that the spin squeezing parameter of Kitagawa and Ueda is a better measure of entanglement than the spectroscopic spin squeezing parameter.